Anatomic-diagnostic and phytochemical features of perspective Polygonum L. species. II (Experimental biology, 2016)
Results on anatomic-diagnostic and phytochemical researches of six Polygonum L. types from the Polygonaceae Juss family are represented. Features of anatomic-diagnostic characters of leaf-plate at the middle-aged generative plants, which have been collected in a blossoming phase, are revealed. It has been proved that distinctive diagnostic characters of Polygonum L. plants is absence or existence of receptacles; anomocytic or anisocytic (diacytic) stoma types; on epidermis formations of tectorial tissue in the form of simple hairs and glands with brownish liquid contents are traced; the peaked nodules of calcium oxalate from the lower party of a leaf and schizogenous intercellular space with liquid red-brown contents more often and also numerous glands with slimy epidermal surface and well developed aeriferous tissue are registered.   Content of alkaloids, anthocyanins, anthraquinones, hydrolysable tannins, xanthones, coumarins, mono- and polysaccharides, flavonoids, amino acids and phenolic acids in six Polygonum L. types from Kazakhstan, by means of phytochemical analysis was shown. Data of the comparative component analysis with authentic samples for the identified structural types of vegetable metabolites are represented. Substances, which allow distinguishing the Polygonum L. plants from Kazakhstan and can be chemo-taxonomical characteristics of species in case of industrial preparations of plants, were identified. Features of a morphological and anatomic structure of plants, which can be used in case of diagnostics of medicinal vegetable raw materials, were revealed.
Keywords: Polygonum L.; features of morphological and anatomic-diagnostic characters of leaf; phytochemical analysis.